Speech Acts Analysis of the Main Characters in Tinder Swindler Documentary Film - Sri Meiweni Basra (JALL (Journal of Applied Linguistics and Literacy), 2023)
Speech acts which belongs to the field of pragmatics carrying a concept that when people say something, they perform an action. The study aims at investigating speech acts in a documentary film entittled the Tinder Swindler. There have been various research on speech acts in movies, but there is a lack of research on this topic which carries a documentary film as the center of attention. A qualitative research method is employed in the research using a document review as the data collection technique and descriptive and interpretative technique to analyze the data. The finding suggests that representative category dominates the utterances in the film taking 74% occurance. Hopefully, this study will fill the research gap and enrich the collection of studies on speech acts.